Mitigation of Selfish Node Attacks in Autoconfiguration of MANETs - Reshmi. T.R; Shymala L; Sandhya. M.K (International Journal of Advances in Applied Sciences, 2018)
Mobile ad-hoc networks (MANETs) are composed of mobile nodes connected by wireless links without using any pre-existent infrastructure. Hence the assigning of unique IP address to the incoming node becomes difficult. There are various dynamic auto configuration protocols available to assign IP address to the incoming nodes including grid based protocol which assigns IP address with less delay and low protocol overhead. Such protocols get affected by presence of either selfish nodes or malicious nodes. Moreover there is no centralized approach to defend against these threats like in wired network such as firewall, intrusion detection system, proxy etc. The selfish nodes are the nodes which receive packet destined to it and drop packet destined to other nodes in order to save its energy and resources. This behavior of nodes affects normal functioning of auto configuration protocol. Many algorithms are available to isolate selfish nodes but they do not deal with presence of false alarm and protocol overhead. And also there are certain algorithms which use complex formulae and tedious mathematical calculations. The proposed algorithm in this paper helps to overcome the attack of selfish nodes effect in an efficient and scalable address auto configuration protocol that automatically configures a network by assigning unique IP addresses to all nodes with a very low protocol overhead, minimal address acquisition delay and computational overhead.